Determination of Temperature, pH, Salinity, Dissolved Oxygen, TDS, TSS, and Nitrite Content in 42-Day-Old Shrimp Farming Ponds - Muhaimin Muhaimin; Putri Meliyani; Dadan Kurnia (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
This study was to determine water quality in shrimps farming through parameters temperature, pH, salinity, Dissolved Oxygen (DO), Total Suspended Solid (TSS), Total Dissolve Solid (TDS) [1,8,2]. Databases for all shrimp farms were created Water quality heavily impacts shrimp health, growth, and disease susceptibility. TDS and TSS were determined by gravimetric analysis, and nitrite was determined by UV-Vis spectrophotometry at 545 nm. Inlets, ponds and outlets were sampled to compare quality differences. The highest temperature (27.9°C) and DO (7.23 mg/L) values were found in the pond, while the inlet had the highest pH (7.54) and salinity (19 psu). TSS (0.055 mg/L) and TDS (20.460 mg/L) were highest in inlet too. The levels of nitrite at the inlet, pond and outlet were an average of 0.0073, 0.0249 and 0.0501 mg/L respectively. Nitrite in shrimp feed was 0.0535±0.0029 mg/L. The analytical parameters for the detection of quercetin were found to have excellent linearity with R² = 0.9959, precision with CV Horwitz ≤10.14%, and accuracy with 90.33–95.04%. The results showed that temperature, pH, salinity, DO, TSS, and TDS levels are suitable and that the acceptable nitrite concentration of the samples fits into the criteria for sustainable shrimp farming